Investigation of Thermal Comfort in UTHM Library - Hariri, Azian; Leong, Tang Kok; A, Djabir (Research Progress in Mechanical and Manufacturing Engineering, 2021)
Educational system becomes agenda in order to produce a dynamic generation in this arena. As such, to reach the objective, the government has established different infrastructures and public buildings such as libraries. Thermal comfort has a crucial impact on the productivity and thermal satisfaction to indoor building’s occupants. This research project presents a study of thermal comfort in Universiti Tun Hussein Onn Malaysia (UTHM) Library. The study aims to produce a mathematical model to predict the comfort air temperature range in UTHM Library. The methodology adopted for the study involves the physical measurement of environmental through TSI VelociCalc Plus air velocity meter and KIMO AMI 310 and personal variables through questionnaire survey. The environmental variables include air temperature (°C), radiant temperature (°C), air velocity (m/s) and relative humidity (%), while the personal variables are metabolic rate (met) and clothing insulation (clo). The data were collected in UTHM Library level two at morning and evening sessions for three days. There were total 60 responses across eight air-conditioned library level two open spaces with 20 responses per day. In general, the findings showed that the subjective response using the questionnaire survey had met the minimum vote of 80% satisfaction. Similarly, the PMV and PPD of -0.10 and 5% for morning session and -0.28 and 7% for evening session respectively were determined by the ASHRAE thermal comfort tool. By using linear regression equation, the relation between air temperature, PMV and TSV were obtained. The results showed that the TSV model was more sensitive than the PMV model but both models still can used for the prediction of comfort air temperature range.